Bending effects study on flexible wearable antenna for 2.45 GHz body centric wireless communications / Aslina Abu Bakar... [et al.] - Abu Bakar, Aslina; Abdul Mustafa, Amirul; Razali, Ahmad Rashidy; Mutalib, Norhayati; Ibrahim, Amirudin (Faculty of Electrical Engineering, 2020)
This study aims to investigate the bending effects on the flexible wearable antenna by using copper nanowires andpolydimethylsiloxane (PDMS). This project focuses on the bending effect on the proposed wearable antenna in the presence of skin tissue and at free space. The radiation characteristics were simulated and analyzed when the antenna was under flat and bent conditions. The performance result of return loss and radiation pattern (E- field and H-field) of proposed wearable antenna was analyzed. The material for the proposed antenna is designed to be flexible and wearable for the application of body-centric wireless communication (BCWCs) at the frequency of 2.45 GHz with the approval specifications of industrial, scientific and medical (ISM) band. Radiator for the proposed wearable antenna is fabricated using copper nanowire, and the antenna substrate is by using polydimethylsiloxane (PDMS). The performance result of the proposed wearable antenna was simulated by using CST microwave studio. From the simulated result for different bending angles, a conclusion was drawn that bending of structure can improve the impedance matching and return loss during the bent condition. However, the resonant frequency tends to shift as the antenna is bent up to 50°. At the critical angle of 70°, the frequency is shifted to a lower frequency.